IMPROVING ENGLISH VOCABULARY TEACHING IN A CHINESE UNIVERSITY ENVIRONMENT - Hou Yu-jing (Universitas Katolik Indonesia Atma Jaya, 2010)
Vocabulary-focusing idea in L2 language acquisition has long been proposed by researchers all over the world, while English vocabulary teaching in Chinese university still remains de-emphasized, especially when compared to the elaborate grammar instruction. Based on the scientific attitude towards vocabulary teaching, the outlines of some principles that should be considered while developing a vocabulary component in a language course under a Chinese university environment are suggested including how to choose appropriate vocabulary-improving materials and how to design a recycling teaching syllabus. Discussing from the pragmatic perspective, the combination of ‘book flood’ program’ together with intensively vocabulary teaching would probably work for Chinese college students.Keywords: English vocabulary teaching, cost-benefit teaching syllabus, pedagogy.